2021
DOI: 10.1108/jima-08-2020-0252
|View full text |Cite
|
Sign up to set email alerts
|

Is Islamic brand attitudes influence Thai Muslims’ buying behavioural intentions: a quantitative analysis using smart-PLS

Abstract: Purpose In southeast Asia, international companies are growing to serve customers with multiple faiths. This study aims to focus on Thailand and it is one of Southeast Asia’s nations and it has Muslim minority customers. To represent Thai Muslim companies, Thai Muslims are marketing their goods by bearing the tagline “we are Islamic”. Scholars described it as “Islamic brands”. This research describes the significant feature of Islamic brands between Thai Muslim people. It examines, which of the Islamic brand d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Besides, according to Aksoy and Abdulfatai (2019), Bananuka et al (2020), Kipnis et al (2019) and Sadiq and Ahmad (2022), culture and religiosity have a positive effect on Muslim consumers’ preferences. Other scholars argued Islamic brand (Abalkhail, 2021; Jan and Shafiq, 2021; Salehzadeh et al , 2021; Singkheeprapha et al , 2021), consumers’ awareness (Islam and Rahman, 2017), materialism (Islam and Chandrasekaran, 2019; Junaidi et al , 2022; Pratono, 2019; Rahman et al , 2017; Ramazani and Kermani, 2021; Zakaria et al , 2021) and commitment (Junaidi et al , 2021; Tabrani et al , 2018) play an important role to influence Muslim decision to adopt Islamic bank. However, the study of religion in marketing has been the sparse and mixed results, such as religiosity has a positive effect on reducing consumers’ view of materialism in Iran (Ramazani and Kermani, 2021), Indonesia (Pratono, 2019) and Malaysia (Amin, 2020b) and profit-sharing governance (Yaya et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, according to Aksoy and Abdulfatai (2019), Bananuka et al (2020), Kipnis et al (2019) and Sadiq and Ahmad (2022), culture and religiosity have a positive effect on Muslim consumers’ preferences. Other scholars argued Islamic brand (Abalkhail, 2021; Jan and Shafiq, 2021; Salehzadeh et al , 2021; Singkheeprapha et al , 2021), consumers’ awareness (Islam and Rahman, 2017), materialism (Islam and Chandrasekaran, 2019; Junaidi et al , 2022; Pratono, 2019; Rahman et al , 2017; Ramazani and Kermani, 2021; Zakaria et al , 2021) and commitment (Junaidi et al , 2021; Tabrani et al , 2018) play an important role to influence Muslim decision to adopt Islamic bank. However, the study of religion in marketing has been the sparse and mixed results, such as religiosity has a positive effect on reducing consumers’ view of materialism in Iran (Ramazani and Kermani, 2021), Indonesia (Pratono, 2019) and Malaysia (Amin, 2020b) and profit-sharing governance (Yaya et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, materialism also possibly bridges religiosity and consumers’ commitment to specific products and services (Adil, 2021; Yaya et al , 2021). Bananuka et al (2020) and Kaawaase and Nalukwago (2017) found that religiosity positively affects the intention to adopt Islamic banking in Uganda and Thailand (Singkheeprapha et al , 2021). Similarly, Lujja et al (2016) concluded that Muslims’ attitudes and social norms have an essential role in influencing people’s decisions.…”
Section: Introductionmentioning
confidence: 99%
“…By using halal or riba -free items, banks that already have an Islamic brand will influence customers’ behaviour and demonstrate that they are committed Muslims (Ahmed et al , 2022; Singkheeprapha et al , 2022; Sukhabot and Jumani, 2023). After the establishment of Islamic branding, customers’ minds will be occupied with the behaviour of a continued intention to use Islamic bank products.…”
Section: Results and Analysismentioning
confidence: 99%
“…According to the most recent research, the Islamic name of a brand, the presence of Halal components in a brand and satisfaction with an Islamic brand in a consumer country are all factors that are considered positives (Jumani and Sukhabot, 2020). Based on the results of a previous study, it was determined that the Islamic brand was developed with the intention of catering to Muslim consumers of goods manufactured in nations that do not practice Islam (Singkheeprapha et al , 2021). It indicates that the Islamic brands by customer perspective of branding concept is appropriate and suggests that the product with the Islamic tag line developed for targeting the customer’s religion (Islam).…”
Section: Discussionmentioning
confidence: 99%